Pengaruh koneksl politis, kepemilikan pemerintah. dan keburaman laporan keuangan femadap kesinkronan dan risil<ocrash harga saham - Purwoto, Lukas ([Yogyakarta] : Fak. Ekonomi UGM, 2011)
Stock price synchrooicity and stock price aash risk are explained in perspective of corporate governance which refers to the lack of intbrmation disclosure. This research investigates the effects of political connections, government ownership, and opaque financial reports on synchrooicity and aash risk of Indonesia-listed firms ftom 2004 to 2008. The degree of both synchrooicity and aash risk is high. Controlling for a number of company characteristics effects, regression analyses show that political connections and government ownership increase stock price synchrooicity. The synchrooicity is also influenced positively by opaque financial reports. Moreover, when financial reports are more opaque. the effects of both political connections and government ownership on synchrooicity tend to increase. These results implicate that the existence of political connections, majority ownership of government, and opacity of financial reporting barrier to supplying of the firm specific intbrmation. Analyses of binary outcome models, which arc controlled by company caractcristics, show that political connections and government ownership do not have positive effects to stock price aash risk in case of transparent financial reports. However, when financial reporting arc more opaque, political connections and government ownership have positive effects on the stock price crash risk. These results arc consistent that both political connection and government owned firms bide bad news or negative intbrmation when submitting poor financial reports.